2016
DOI: 10.1177/0255761415619427
|View full text |Cite
|
Sign up to set email alerts
|

How do undergraduate piano students memorize their repertoires?

Abstract: This study investigated the routine procedures employed by nine undergraduate piano students at a Brazilian university while learning and performing memorized pieces and the procedures employed using Chaffin's performance cue (PC) protocols. The data were collected in two phases. In Phase I, each participant selected one piece that he or she had previously studied and memorized in the preceding academic semester. For Phase II, the students were introduced to Chaffin's PC protocols, and they were allowed 10 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The pianists also reported using a segmented approach to practice, which actually appears to be a favoured method among experienced musicians in other styles of repertoire (Chaffin & Imreh, 2001; Gerling & Dos Santos, 2017; Mishra, 2005). Previous research has found that musical structure is often used as a criterion to segment practice and to guide encoding and retrieval (Williamon & Egner, 2004; Williamon & Valentine, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The pianists also reported using a segmented approach to practice, which actually appears to be a favoured method among experienced musicians in other styles of repertoire (Chaffin & Imreh, 2001; Gerling & Dos Santos, 2017; Mishra, 2005). Previous research has found that musical structure is often used as a criterion to segment practice and to guide encoding and retrieval (Williamon & Egner, 2004; Williamon & Valentine, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The student pianists who participated in a study by Davidson-Kelly et al (2012) reported preferring physical strategies (e.g., practising slowly, with hands separately, varying notated rhythms) to mental strategies (e.g., analysing the music and memorising it before beginning to play). Gerling and Dos Santos (2017) found that pianists memorising Classical and Romantic works deliberately memorised kinaesthetic cues including awareness of the direction in which their hands moved at particular locations in the music, and developed their procedural knowledge of what they referred to as the topography of the keyboard and its association with the type and direction of their body movements.…”
Section: Research On Musicians' Memorising Strategiesmentioning
confidence: 99%
“…To improve music recognition accuracy, the two characteristics of music rhythm and pitch are extracted and compared. A multiclass and hierarchical music retrieval method was proposed in the literature [20]. To divide the audio signal into different sound types, first set the environmental noise segment, then extract the statistical music-related feature data to divide the audio signal into music segment, environment segment, silent segment, and so on.…”
Section: Related Workmentioning
confidence: 99%